Conservation biological control in forest: A case study with the pine processionary moth - Nattan Plat; Lucas Moreews; Laura Schillé; Jean-Baptiste Rivoal; Hervé Jactel (Biological Control)
In forest ecosystems, the damage caused to trees by insect pests is increasing as a result of global change. Classical biological control has proven effective in managing exotic pests by introducing natural enemies from the pest’s native range. For native pests, however, conservation biological control, which aims to improve the habitats and resources for native natural enemies, is more appropriate. While widely studied in agricultural systems, this method has been rarely, if ever, tested in forest. In this study, we aimed to test whether broadleaved hedgerows could improve the control of the pine processionary moth (Thaumetopoea pityocampa) in adjacent pine stands by providing a favorable habitat for an insectivorous bird, the great tit (Parus major). To this end, we assessed PPM infestations on the edges of pine plantations adjacent to broadleaved hedgerows or mature pine plantation, recorded the vocal activity of great tit using sound recorders, and experimentally measured bird predation using dummy caterpillars. The density of processionary caterpillar nests was lower at the edge of pine stands adjacent to hedgerows than at the edge adjacent to mature pine stands. We showed that bird predation was more frequent on pine edges adjacent to hedgerows. Predation by birds was also positively correlated with the vocal activity of the great tit, the main predator of pine processionary caterpillars in winter. In conifer monocultures, broadleaved hedgerows not only help to control the pest but could also promote biodiversity and protect pine plantations from abiotic hazards, thereby enhancing the multifunctionality of plantation landscapes.